AB0018 TNFΑ RS1800629 POLYMORPHISM: WHAT ABOUT ITS ASSOCIATION WITH CLINICAL MANIFESTATIONS AND ANTI-TNFΑ THERAPY? DATA FROM A SERIES OF ITALIAN PATIENTS WITH BEHÇET SYNDROME. (2nd June 2020) - Padula, M. C.; Leccese, P.; Lascaro, N.; Sorrento, G. G.; Radice, R. P.; Limongi, A. R.; Carbone, T.; Padula, A.; Martelli, G.; D'angelo, S.
Abstract : Background: Tumor Necrosis Factor-alpha (TNF-α) is a pleiotropic cytokine with a critical role in the pathogenesis of Behçet syndrome (BS). Anti-TNF-α therapy is useful for patients with refractory, severe BS, in particular for ocular, central nervous system, and gastrointestinal manifestations. However, although biological treatment with anti-TNF-α agents are effective in BS, not all patients are definite responders. Non-responders patterns could be due to: alternative non-TNFα related pathway of inflammation; anti-drug antibodies presence or development; polymorphic alleles of TNFα gene. TNFα rs1800629 (-308G>A) is a drug-response single nucleotide polymorphism (SNP) located within the gene promoter. Poor and conflicting data are currently available about the association of this polymorphism and clinical manifestations of BS, as well as about the responsivness to the TNFα blockers in BS patients [1-3]. Objectives: Aims of this study were to investigate in a cohort of Italian patients with BS the frequency of rs1800629 genotypes and its association with clinical features and anti-TNFα therapy response. Methods: Consecutive patients with BS were recruited. Patients demographic and clinical data were collected by medical records and analyzed. Home-made specific primer pairs were used for rs1800629 coverage. gDNA was isolated and amplified using PCR. Good-quality amplicons were sequenced (Sanger method). In silico analysis was downstream performed using specific software for query-subject similarity analysis. Results: 130 BS patients (64M:66F; mean age: 45.8±12.3 years) were included in the study. Patients predominant lesions were oral aphtosis (100%), eye involvement (86.2%), skin lesions (72.3%) and genital ulcers (57.7%). TNFα rs1800629 wild-type GG genotype was found in 106/130 BS patients (81.5%); the heterozygous genotype (GA) was identified in 24/130 patients (18.5%). No statistically significant differences were found in genotypes frequencies when the patients were stratified for presence and absence of each clinical manifestation (p>0.05), while statistical significant differences were found when the patients were compared for therapy (anti-TNFα drugs) response. In detail, 73/130 patients (56.2%) were treated with anti-TNFα agents. We found 16/73 (21.9%) non-responders patients (NRP). In NRP group, we identified 9/16 patients (56.3%) with GG genotype and 7/16 (43.7%) with GA genotype, while 8/57 (14.0%) responder patients showed GA genotype and 49/57 responder patients (86.0%) showed GG genotype (p=0.0093; OR: 0.21, CI: 0.06-0.729). Conclusion: Here we described a low frequency of TNFα rs1800629 SNP-containing allele and the lack of association between SNP and BS clinical hallmark, as previously reported in literature [1-4]. We also found higher percentage of GG genotype in case of therapy response than GA genotype. The SNP is a promoter polymorphism that could affect the auto-inflammatory response and the therapy responsivness, as suggested by our preliminary data of pharmacogenomics. Analyses of a larger cohort of patients are need to confirm the study findings and to explain the SNP role as outcome predictor. References: [1]Touma Z et al. (2010). Arch Med Res 41(2):142-6; [2]Vallet H et al. (2015). J Autoimmun 62:67-74. [3]Zhang M et al. (2013). Mol Vis 19:1913-24. [4]Ateş A et al. (2006). Rheumatol Int 26(4):348-53. Disclosure of Interests: Maria Carmela Padula: None declared, Pietro Leccese: None declared, Nancy Lascaro: None declared, Giusi Gaia Sorrento: None declared, Rosa Paola Radice: None declared, Antonina Rita Limongi: None declared, Teresa Carbone: None declared, Angela Padula: None declared, Giuseppe Martelli: None declared, Salvatore D'Angelo Consultant of: AbbVie, Biogen, BMS, Celgene, Eli Lilly, MSD, Novartis, and UCB, Speakers bureau: AbbVie, BMS, Celgene, Eli Lilly, Novartis, Pfizer, and Sanofi